2010
DOI: 10.1088/0957-0233/22/1/015401
|View full text |Cite
|
Sign up to set email alerts
|

On the calibration of astigmatism particle tracking velocimetry for microflows

Abstract: Astigmatism particle tracking velocimetry (APTV) is a method to determine three components (3C) of the velocity field in a volume (3D) using a single camera. The depth position of the particles is coded by optical distortions caused by a cylindrical lens in the optical setup. This technique is particularly suited for microfluidic applications as measurement errors due to spatial averaging and depth of correlation, typically encountered with μPIV approaches, are eliminated so that the measurement precision is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
116
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 18 publications
4
116
2
1
Order By: Relevance
“…A fully three-dimensional evaluation of the particle trajectories and velocities was performed by means of the astigmatism particle tracking velocimetry (APTV) technique [33,34] coupled to the temperature-controlled and automated setup presented in Ref. [28].…”
Section: Methodsmentioning
confidence: 99%
“…A fully three-dimensional evaluation of the particle trajectories and velocities was performed by means of the astigmatism particle tracking velocimetry (APTV) technique [33,34] coupled to the temperature-controlled and automated setup presented in Ref. [28].…”
Section: Methodsmentioning
confidence: 99%
“…The basic principle of astigmatism µ-PTV is that due to the anamorphic effect by inserting a cylindrical lens, particle images are deformed into ellipses. This ellipticity is directly related to the particle position normal to the focal plane (Liu et al 2014a;Cierpka et al 2010Cierpka et al , 2011Cierpka and Kähler 2012). A fluorescence microscope with a 20× Zeiss objective lens (numerical aperture of 0.4 and focal length of 7.9 mm) was used.…”
Section: Methodsmentioning
confidence: 99%
“…1 3 (Liu et al 2014a;Cierpka et al 2010Cierpka et al , 2011Cierpka and Kähler 2012). The vorticity is analyzed as function of the axial background velocity and the results are compared to a numerical model developed before (Liu et al 2014b).…”
mentioning
confidence: 99%
“…Experimental investigations have shown that μPIV [11][12][13] and PTV 14,15 are powerful tools for analysing 2D microchannel acoustophoresis. Fully 3D particle tracking has been demonstrated using μPIV with depth of correlations 16 and astigmatism particle tracking velocimetry [17][18][19] . On the other hand, numerical simulations of acoustophoretic motion of microparticles can provide efficient prediction of experiments and provide effective guidance and optimization on the design of acoustofluidic devices to enhance or improve experiments.…”
Section: Introductionmentioning
confidence: 99%